(untitled) (Global Journal of Management and Business Research, 2020)
Employee innovation is one of the most critical factors which affects the overall growth of an organization. To get innovative ideas out of an organization’s employees, incentives play a vital role. In this paper, different incentive structures from previous researches has been examined that are followed by top management for generating innovative ideas. Although most researches from the past found that a fixed wage or compensation based on performance induces a high level of innovation, but it is actually detrimental for innovation. Rather rewarding employees for long term or performance-based promotion is more effective in fostering innovation. From my evidence and based on the articles analyzed in this paper it was found that performance-based promotion is more fruitful for innovation.